PENGUKURAN KINERJA UMKM MELALUI FAKTOR INTERNAL DAN FAKTOR EKSTERNAL : STUDI KASUS PADA UMKM GULA KELAPA DI KABUPATEN BANYUMAS - Isnaeni Rokhayati; Herwiek Diyah Lestari (Majalah Imiah Manajemen & Bisnis, 2020)
The purpose of this study is measuring the performance of Micro, Small and Medium Enterprises (SMEs) views of factors and Internal external factors. Internal factors such as human resources, finance, production and marketing. While external factors can be seen from the technology, government policy, social economy and the role of institutions. Performance of SMEs can be seen from the various growth occurring in SMEs as sales growth, capital growth, employment growth, profit growth, and the growth of the market. This research is a survey directly to the respondent by means of direct interviews and questionnaires. Samples were obtained as many as 160 respondents coconut sugar SME owners across Banyumas district. Analysis of experimental data was analyzed with descriptive statistics and srutuctural equation modeling (SEM) using AMOS 4.01 program and SPSS for windows. By knowing the performance of SMEs is expected to increase the welfare of the owners of SMEs and SMEs can develop their business and be able to compete in today's global marketplace.